C1-C2 alkyl aminiums in urban aerosols: Insights from ambient and fuel combustion emission measurements in the Yangtze River Delta region of China. (November 2017) - Shen, Wenchao; Ren, Lili; Zhao, Yi; Zhou, Luyu; Dai, Liang; Ge, Xinlei; Kong, Shaofei; Yan, Qin; Xu, Honghui; Jiang, Yujun; He, Jun; Chen, Mindong; et al.
Abstract: We measured low molar-mass alkyl aminiums (methylaminium, dimethylaminium, ethylaminium and diethylaminium) in urban aerosols in the Yangtze River Delta region of eastern China in August 2014 and from November 2015 to May 2016. After examining artifact formation on sample filters, methylaminium, dimethylaminium and ethylaminium concentrations were quantified. The three C1-C2 aminiums exhibited a unimodal size distribution that maximized between 0.56 and 1.0 μm. Their concentrations in PM2.5 were 5.7 ± 3.2 ng m −3, 7.9 ± 5.4 ng m −3 and 20.3 ± 16.6 ng m −3, respectively, with higher concentrations during the daytime and in warm seasons. On new particle growth days, amine uptake to particles larger than 56 nm was barely enhanced. The molar ratios of individual aminium/NH4 + in PM2.5 were on the order of 10 −4 and 10 −3 . Aminiums were thus far less to out-compete ammonium (NH4 + ) in neutralizing acidic species in particle sizes down to 56 nm. Abundant nitrate (NO3 − /SO4 2− molar ratio = ∼3) and its correlation to methylaminium and ethylaminium implied that nitrate might be more important aminium salt than sulfate in urban aerosols of this area. Direct measurement of particle-phase amine emission from coal and biomass burning showed that coal burning is an important atmospheric amine source, considering coal burning is top-ranked particulate matter source in China. Graphical abstract: Highlights: Aminium concentration showed seasonal and diurnal variations in urban aerosols of our area. Nitrate was more important aminium salt than sulfate in urban aerosols of our area. Particle-phase amine emission from coal burning is an important atmospheric amine source. Amine uptake to particles larger than 56 nm was barely enhanced on new particle growth events. Aminiums cannot out-compete ammonium in neutralizing acidic species in urban aerosols with particle sizes down to 56 nm. Abstract : Aminiums cannot out-compete ammonium in neutralizing acidic species in particle sizes down to 56 nm. Their uptake to particles >56 nm was barely enhanced on new particle growth days. Coal burning is an important atmospheric amine source.